In Her Multimedia Words: Ukrainian Women in The Netherlands, Belonging and Temporary Protection Status - Noemi Mena Montes; Colleen Boland (Social Sciences, 2025)
Recent research in digital migration studies analyzes both refugee populations’ social media use and so-called integration outcomes. Against the backdrop of digitalization, we argue for understanding belonging as part of an ongoing process in physical, virtual and hybrid continuities, where material aspects cannot be divorced from imagined constructions. We take the case of Ukrainian women arriving in the Netherlands following the Russian aggression against Ukraine, in 15 semi-structured interviews from 2023. Adopting an intersectional lens, our research asks the following questions: How does social media use mediate or inform a sense of belonging? How do observations correspond to or differ from previous studies on refugees and social media, given this population’s temporary protection (TP) status? As participants leverage digital platforms differently in evolving situations, they navigate connectedness to the new community; we argue this may be linked to distinct TP status and other characteristics of difference, including educational levels and digital literacy. Conclusions indicate that an intersectional lens could be applied in understanding Ukrainian perspectives in other Member States—or beneficiaries of differing origin—to better account for how intersectional dimensions like legal status can be mutually constitutive of virtual connectedness versus material, physical rootedness or vulnerability.